PENGARUH ATMOSPHERE RITEL TERHADAP KEINGINAN MEMBELI MASYARAKAT DI KOTA PADANG - Tri Rachmat Riski, Heru Aulia Azman, (Jurnal Ekonomi, 2016)
The atmosphere of retail shall fucntion as kind of stmuli that will attract the visitor to decide which store to choose. Further, it was aimed to evoke the desire of visitors to purchase and create transaction.the purpose of this study was to determine the impact of atmosphere of the retail on the intention to buy among visitors. Explanatory research and survey researh was conducted by spreading 100 questionaires to visitors. The result of the study found that (1) according to partially colour and displayhave significant influence toward intention to Â buy, and partially cleanness, music, smell, temperature, and lighting did not have significant influence toward intention to Â buy, and (2) in a manner of simulate the retail atmosphere has significant influence toward intention to buy